2011
DOI: 10.1007/s11135-011-9591-1
|View full text |Cite
|
Sign up to set email alerts
|

National minorities and their representation in social surveys: which practices make a difference?

Abstract: This paper presents a systematic study of survey mechanisms that produce or reduce minority bias in social surveys. It extends the work of who have demonstrated that, in the Swiss context, the more an ethno-national minority community differs, socio-culturally and socio-economically, from the national majority, the less it is likely to be represented in its proper proportion in the major national surveys. Minority bias furthermore has a vertical dimension: socio-economic bias against individuals from the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 8 publications
4
29
0
1
Order By: Relevance
“…However, the implemented procedure is not without some limitations. For example, in such studies some less well-integrated subgroups (such as individuals with poorer health or low language skills) could be more difficult to contact and convince to participate (Laganà et al 2011). Consistent with previous studies (e.g., Aluja et al 2007;Riva et al 2003), the first analyses indicated no differences in the evaluation of psychological processes related to survey format.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the implemented procedure is not without some limitations. For example, in such studies some less well-integrated subgroups (such as individuals with poorer health or low language skills) could be more difficult to contact and convince to participate (Laganà et al 2011). Consistent with previous studies (e.g., Aluja et al 2007;Riva et al 2003), the first analyses indicated no differences in the evaluation of psychological processes related to survey format.…”
Section: Discussionsupporting
confidence: 71%
“…This limitation -which is not uniquely related to the mixed-mode method -is probably more important among non-Swiss individuals and subgroups with higher levels of low skilled people (such as unemployed individuals). Nevertheless, as indicated by Laganà et al (2011), reaching more marginal groups -for example due to language limitations -is a recurrent problem in this kind of survey. Finally, online surveys, similar to surveys based on phone interviews, are affected by coverage bias (or error) (i.e., not all the household are equipped with Internet or phone connections, and coverage could differ within groups, e.g., lower-income vs. higher-income) (de Leeuw 2005).…”
Section: Why Use a Mixed-mode Method?mentioning
confidence: 99%
“…As for the total resident population 65 and over, there was an increase of 21 % from 1995 to 2010, while the foreign population increased 55 % in the same period of time (Swiss Federal Statistical Office 2012). rate and ethno-social affiliations Elcheroth et al 2011;Laganà et al 2013). These studies conclude that the underrepresentation of national minorities results in bias even after controlling for socioeconomic status.…”
Section: Surveying Elderly Migrants As An Illustration Of Surveying Vmentioning
confidence: 90%
“…Not speaking the survey language is one factor. But having living conditions that make someone uneasily reachable by standard procedures or having a system of beliefs and values that make the questions not understandable constitute major difficulties as well (Feskens et al 2006;Lipps et al 2011;Elcheroth et al 2011;Laganà et al 2011). Moreover, analysis of reasons for inclusion and exclusion of national minority groups from Swiss large-scale surveys confirms the relation between nonresponse population" submitted twice to the vote of the Swiss population in the 1970s.…”
Section: Surveying Elderly Migrants As An Illustration Of Surveying Vmentioning
confidence: 99%
“…or to have lower literacy in the language of the questionnaire (Groves and Couper 1998;Stoop 2005). For Switzerland, earlier findings show that immigrant groups from non-EU countries are usually underrepresented in surveys (Laganà et al 2011;Lipps et al 2013). It is thus important to understand the mechanism behind nonresponse and, if possible, to correct for it.…”
Section: Survey Biasmentioning
confidence: 98%